2016
DOI: 10.1039/c5sc04062k
|View full text |Cite
|
Sign up to set email alerts
|

Combining photochemistry and catalysis: rapid access to sp3 – rich polyheterocycles from simple pyrroles

Abstract: The powerful combination of photochemistry and catalysis transforms simple pyrroles into complex polycyclic structures in just two steps. Initial formation of highly reactive aziridines enables new Pd-catalysed cascade sequences, forming a range of polyheterocycles including tricyclic β-lactams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Stimulated by the ground-breaking works of the Seeberger [4142 47,5051], Booker-Milburn [5253], and Noël [34,5455] groups in recent years, we therefore decided to develop our own home-made flow reactor for photooxidations of organic molecules but also envisaged its general applicability to other challenging processes with the ternary “reagent” combinations liquid/gas/light. With the objective of constructing a robust and versatile flow reactor, we set out to explore and test commercially available parts.…”
Section: Resultsmentioning
confidence: 99%
“…Stimulated by the ground-breaking works of the Seeberger [4142 47,5051], Booker-Milburn [5253], and Noël [34,5455] groups in recent years, we therefore decided to develop our own home-made flow reactor for photooxidations of organic molecules but also envisaged its general applicability to other challenging processes with the ternary “reagent” combinations liquid/gas/light. With the objective of constructing a robust and versatile flow reactor, we set out to explore and test commercially available parts.…”
Section: Resultsmentioning
confidence: 99%
“…This differencei nr eactionr ate was intriguing, both from at heoretical point of view and because ab etter understanding of the factorsa ccelerating this reactionm ight help minimise its competition as as ide reactioni no ther transformations. [7] Additionally,p revious studies,m ost notably those of Somfai, [9a,b] had generally shown this typeo f[ 1,5]-hydrogen shift to be facile only when an activating group (e.g.,e ster, phenyl) wasp resent at the migration origin. Subsequents tudies by Somfai of the [1,5]-hydrogen shift reactions of various substituted, conformationally flexible vinyl aziridines showed relativelys mall differences in reaction rate unless the alkene geometry was varied.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, substrates 5 , 7 and 9 were seen to undergo conversion to the imine product at room temperature. This difference in reaction rate was intriguing, both from a theoretical point of view and because a better understanding of the factors accelerating this reaction might help minimise its competition as a side reaction in other transformations . Additionally, previous studies, most notably those of Somfai,, had generally shown this type of [1,5]‐hydrogen shift to be facile only when an activating group (e.g., ester, phenyl) was present at the migration origin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, various interesting palladium-catalysed transformations in a continuous flow have also been reported over the last five years. The scientific reports include transformations such as oxidation, reduction, cyclopropanation, desulfinative C-C cross-coupling, photochemical aziridine synthesis 46 and trifluoromethylthiolation. 47 In 2017, Kappe et al described a continuous flow protocol for a Pd-catalysed olefin cleavage using gaseous oxygen.…”
Section: Syn Thesis 5 Miscellaneous Reactionsmentioning
confidence: 99%